The Stratification of Abu al-Shiddiq (w. 108 H) and Qatadah (w. 118 H) in the Narration of the al-Mahdi Hadith - Kinkin Syamsudin; M. Dede Rodliyana (IAIN Pekalongan, 2022)
This article discusses the presence or absence of different effects in rawi stratification on hadith narration. The research used was the study of libraries with a content analysis approach based on Ibn Khaldun's stratification theory in the book of Muqaddimah. The study focused on the hadiths of al-Mahdi narrated through the path of Abu al-Shiddiq (d. 108 H) and Abu Nadhrah (d. 103 H). It was found that Qatadah was abu al-Shiddiq's disciple who received the most history, but specifically the history of al-Mahdi he did not receive from him but from another teacher named Abu Nadhrah. The three narrations are both considered as rawi tsiqah, but they have differences in stratification that can expressly be seen the number of hadiths narrated. Qatadah has a history of 12,209, while Abu al-Shiddiq 183 and Abu Nadhrah 1,181. By compiling Ibn Khaldun's stratification theory and data on the number of histories owned by these three rawi people, it is concluded that the difference in stratification between Abu al-Shiddiq, Abu Nadhrah and Qatadah is not the reason Qatadah was not involved in the narration of al-Mahdi hadith from Abu al-Shiddiq.